1997
DOI: 10.1183/09031936.97.10071552
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the treatment of non-small cell lung cancer (NSCLC) in England and Wales

Abstract: Six hundred and ninety eight (85%) of the 821 clinicians responded. For Case 1, 74% would not recommend any adjuvant treatment, 24% would recommend radiotherapy, and <1% chemotherapy, and there was little expectation that adjuvant treatment would improve survival. For Case 2, 68% would recommend radiotherapy, 11% chemotherapy, and 1% surgery, 7% recommending a combination. Adjuvant treatment, regardless of modality, was expected to improve survival. For Case 3, only 11% would recommend chemotherapy, but 26% if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…This trial was designed to investigate and compare immediate versus delayed thoracic radiotherapy in patients with inoperable NSCLC, as there exists some doubt as to the clinical beneÿt of immediate radiotherapy for those patients with NSCLC (Carroll et al [10], Crook et al [11]). Articles by Phillips and Miller [12] and Cox et al [13] advocate immediate thoracic radiotherapy, suggesting that one may achieve a prolonged survival and may also improve a patient's quality of life.…”
Section: A Trial Of Radiotherapy In Non-small Cell Lung Cancermentioning
confidence: 99%
“…This trial was designed to investigate and compare immediate versus delayed thoracic radiotherapy in patients with inoperable NSCLC, as there exists some doubt as to the clinical beneÿt of immediate radiotherapy for those patients with NSCLC (Carroll et al [10], Crook et al [11]). Articles by Phillips and Miller [12] and Cox et al [13] advocate immediate thoracic radiotherapy, suggesting that one may achieve a prolonged survival and may also improve a patient's quality of life.…”
Section: A Trial Of Radiotherapy In Non-small Cell Lung Cancermentioning
confidence: 99%
“…Physician skepticism regarding the benefits of chemotherapy for NSCLC has been reported by Raby et al, who found that only 20% of Canadian physicians surveyed thought that treating advanced NSCLC with chemotherapy was worthwhile [9], and by Crook et al in Great Britain, who reported that 11% of clinicians would recommend chemotherapy for appropriate patients, with that proportion rising to 26% if the patient was less than 50 years old [10].…”
Section: Introductionmentioning
confidence: 95%
“…It is well recognized that many cancer treatments are not provided in accordance with the best available clinical evidence [1][2][3][4][5][6][7]. This problem has been addressed in part by the development of clinical practice guidelines (CPGs), that have been used not only to assist clinical decision making, but have also been used as a benchmark to evaluate the treatment provided in the community [5,6,8].…”
Section: Introductionmentioning
confidence: 99%